Health after union dissolution(s): Cumulative and temporal dynamics - Anna Barbuscia; Emmanuelle Cambois; Ariane Pailhé; Chiara Ludovica Comolli; Laura Bernardi (Elsevier, 2022)
The number of individuals experiencing one or multiple union dissolutions in their lifetime is increasing. The literature has shown significant interactions with health disorders, in response to the crisis situation that affects the spouses. However, processes are still unclear, in particular regarding the timing of the affection. This study explored whether different health disorders are observed shortly after dissolution or are delayed, and whether they are short- or long-lasting. We used data from the two waves (2006 and 2010) of the French Health and Professional Lives Survey (SIP) among 8349 individuals aged 25-64 years. Based on three health disorders, we studied 1) their levels in relation to the retrospective histories of union dissolutions; 2) health changes associated with a dissolution occurring between the two waves. We found that individuals who experienced one or multiple union dissolutions had worse self-rated health, more depressive symptoms and sleep disorders. The two latter were more related with a recent dissolution than with distant ones, suggesting an immediate association, yet long-lasting. Self-rated health was related with distant dissolutions only, suggesting a lagged, however also long-lasting association. Experiencing union dissolution between the two waves was linked to a higher probability of the onset of sleep disorders and depressive mood, and of deterioration of self-rated health if it was not the first dissolution. Our study shows that union dissolutions are highly correlated with different poor health measures, in the short and the long run, depending on the health disorder, with cumulative and durable effects.